Enlisting in the army in the Jewish Ultraorthodox community and the consequences for wellbeing - Malovicki-Yaffe, Nechumi; Itzhaki-Braun, Yael; Shahar-Rosenblum, Shomi (Frontiers in Psychology, 2023)
Israeli law requires citizens to enlist in the army at 18 years old. However, the Jewish Ultraorthodox community has a longstanding agreement with the state that members of this community will not have to enlist in the army, given its spiritual leaders’ strong opposition. Still, there are young men who go against the communal norms and enlist. In the current study we investigated these young men and the contribution of their self-esteem (a personal resource), their sense of community (a communal resource), and the community members’ attitudes toward them (societal conditional regard, both positive and negative, and stigma) to their well-being. The current study consisted of 153 participants between the ages of 20 and 55 (M=29.64, SD=6.89), A path analysis model indicated the protective role played by self-esteem and sense of community in participants’ well-being, and the risk factor posed by societal conditional negative regard and stigma. Moreover, self-esteem was found to mediate between income and well-being, whereas sense of community was found to mediate between societal conditional negative regard and well-being, and between stigma and well-being. The discussion highlights the complexity of the protective role played by sense of community against the risk of experiencing societal conditional negative regard and stigma. It also addresses the importance of promoting intervention programs during the army service of these young men, with a focus on promoting their self-esteem and on the presence of a spiritual leadership that legitimizes working, serving in the army, and yet still being part of the community.